MENINGKATKAN HASIL BELAJAR PKN MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS IV SD NEGERI 012 SILIKUAN HULU KECAMATAN UKUI - Sudahana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by low Civics learning outcomes among students. The low level of achievement was caused by several factors: (a) teaching methods applied by teachers tended to be passive and monotonous; and (b) students were more inclined to engage in off-task behavior during lessons. This study aimed to improve students’ Civics learning outcomes. The research employed classroom action research conducted at SD Negeri 012 Silikuan Hulu. The data used in this study included observations of teacher and student activities as well as students’ Civics learning outcomes. The results of the study revealed improvements in both teacher and student activities, which were followed by increased student learning outcomes. This improvement was evidenced by the following findings: based on preliminary data, only 10 students achieved mastery. In the first cycle, the number of students who completed the learning objectives increased to 15, and further increased to 17 students in the second cycle. Teacher activity also showed improvement, with the percentage of teacher activity increasing from 47% in the first meeting of the first cycle to 56% in the second meeting. In the second cycle, teacher activity rose to 68% in the first meeting and further increased to 73% in the second meeting. Similarly, student activity increased across the cycles. In the first cycle, student activity reached 50% in the first meeting and rose to 57% in the second meeting. In the second cycle, student activity increased to 65% in the first meeting and reached 82% in the second meeting. These results indicate that improvements in teaching practices and student engagement contributed to better Civics learning outcomes.